Handbook of environmental impact assessment (Blackwell Science, 1999)
Environmental Impact Assessment (EIA) is a significant, anticipatory, environmental management tool. International debate focuses on its enhancement to meet the challenges of sustainable development and demands for scientifically robust integrated and participative decision-making. This handbook hopes to improve practice by contributing an international, multidisciplinary, ready-reference source to this debate. Volume I addresses EIA principles, process and methods. Part 1 maps the EIA process and its impact on decision, and positions EIA in the context of sustainable development as well as the other decision tools, including economic valuation. It also positions strategic environmental assessment (SEA) in a similar way. Part 2 addresses the elements of the EIA process and significant impact assessment topics (air, water, ecological, social, risk, landscape and visual), not only in terms of good practice but also methodological evolution. The volume concludes by addressing cumulative impact assessment and SEA methods.